Bilateral High Signal Intensity on DWI of the Precentral Cortices in Mitochondriopathy Due to MTO1 Mutation and MT-TF Variant. (9th February 2021) - Dorcet, Guillaume; Fabry, Vincent; Bonneville, Fabrice; Cintas, Pascal
Abstract : A 40-year-old woman and her 38-year-old brother developed since childhood optic neuropathy, absence epilepsy, cognitive disability, cerebellar syndrome, hypertrophic cardiomyopathy, and scoliokyphosis, due to a mitochondriopathy associating MTO1 mutation and an MT-FT variant, both genes involved in mitochondrial tRNA modification. 1 Brain MRIs were normal during childhood, but cortical, symmetric hyperintensities of precentral gyri on diffusion-weighted imaging (figure) arose apart from any new symptom, different from previously reported MTO1 mitochondriopathies, only noncortical, 2 from status epilepticus, generally unilateral and associated with a thalamic or corpus callosum splenium hypersignal, and from Creutzfeldt-Jakob disease, usually more posterior and associated with pulvinar and basal ganglia hyperintensities.